Cobalt‐Catalyzed Markovnikov‐Type Selective Hydroboration of Terminal Alkynes. Issue 2 (10th November 2020) - Chen, Jieping; Shen, Xuzhong; Lu, Zhan
Abstract: A cobalt‐catalyzed Markovnikov‐type hydroboration of terminal alkynes with HBpin to access α‐alkenyl boronates with good regioselectivity and atom economy is reported. A new ligand has been developed for the cobalt hydride catalyst that has been used for a unique Markovnikov selective insertion of terminal alkynes into metal hydride bond. This operationally simple protocol exhibits excellent functional group tolerance to deliver valuable alkene derivatives. Abstract : A cobalt hydride catalyst has been developed to promote Markovnikov‐type selective insertion of the terminal alkyne to access branched alkenyl boronates. This method exhibits high atom economy and broad substrate scope with excellent functional group tolerance.